Minus plastic : applying stages of change to an environmental promotional campaign. - Chiew, Han Joo. (2009)
Plastic have much to offer as a modern convenience but if we do not take responsibility in developing proper plastic waste management habits, plastic can have potential harmful effects on the environment. Secondary research revealed the lack of focus on youth attitudes and needs in existing environmental initiatives. [minus]plastic is an environmental public promotional campaign targeted at Singaporean youth aged between 17 and 25 years. The campaign encouraged youth to adopt positive attitudes towards responsible plastic management, recognise the importance of and subsequently adopt the practice of responsible plastic management. The two-month long youth-for-youth campaign is one of Singapore’s pioneering projects on reducing plastic usage. This study utilised Prochaska and DiClemente’s stages of change model (1982) as the overarching theory to study current youth attitudes towards environmental concerns. A pre-post quantitative research design showed that the pre-contemplation, contemplation and preparation stages progressed significantly after the campaign. The implications from the study are specialised information must be adapted to the different stages to allow migration to the next stages. With strong presence of Internet culture among Singaporean youth, the online medium was proven effective in altering the attitudes of the target audience. Therefore future environmental campaign targeted at youth could explore this platform to disseminate their messages.